2014
DOI: 10.1002/ajh.23743
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 versus Type 2 calreticulin mutations in essential thrombocythemia: A collaborative study of 1027 patients

Abstract: CALR (calreticulin) trails JAK2 as the second most mutated gene in essential thrombocythemia (ET). Mutant CALR in ET is a result of frameshift mutations, caused by exon 9 deletions or insertions; type-1, 52-bp deletion (p.L367fs*46), and type-2, 5-bp TTGTC insertion (p.K385fs*47) variants constitute more than 80% of these mutations. The current study includes a total of 1027 patients divided into test (n 5 402) and validation (n 5 625) cohorts. Among the 402 ET patients in the test cohort, 227 (57%) harbored J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
151
6
4

Year Published

2015
2015
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 186 publications
(182 citation statements)
references
References 18 publications
21
151
6
4
Order By: Relevance
“…However, this observation was not supported by subsequent other studies while other reports suggested differential prognostic effects from distinct mutant CALR variants in PMF [6,8,12,13]. In ET, patients with type 2 CALR mutations displayed significantly higher platelet count, compared to their counterparts with type 1 CALR mutations [17]. In the latter study, overall and thrombosis-free survivals (TFS) were similar between the two groups of CALR-mutated patients.…”
Section: Introductionmentioning
confidence: 62%
“…However, this observation was not supported by subsequent other studies while other reports suggested differential prognostic effects from distinct mutant CALR variants in PMF [6,8,12,13]. In ET, patients with type 2 CALR mutations displayed significantly higher platelet count, compared to their counterparts with type 1 CALR mutations [17]. In the latter study, overall and thrombosis-free survivals (TFS) were similar between the two groups of CALR-mutated patients.…”
Section: Introductionmentioning
confidence: 62%
“…JAK2 exon 12 mutation positive patients usually present with predominantly erythroid myelopoiesis, subnormal serum erythropoietin level and younger age at diagnosis, but were prognostically similar to JAK2V617F [28]. In ET, mutant CALR (vs. JAK2) was associated with younger age, male sex, higher platelet count, lower hemoglobin level, lower leukocyte count, and lower incidence of thrombotic events [9][10][11][12]; Type 2 versus Type 1 CALR mutations were associated with higher platelet count [29]. In PMF, CALR-mutated patients were also younger and presented with higher platelet count, better risk profile, and lower frequencies of anemia, leukocytosis, and spliceosome mutations [13].…”
mentioning
confidence: 97%
“…del52 and ins5 CALR mutants might stabilize 2 related, but not identical, active dimeric interfaces of TpoR, leading to differences in the phenotype, as suggested. 41,42 This hypothesis would also explain why CALR mutants are not seen in other cancers driven by N-glycosylated mutated receptors (eg, EGFR, EPOR, KIT, FLT3D). 6 Furthermore, binding of CALR mutant to TpoR and its activation do not require Tpo-binding.…”
Section: Discussionmentioning
confidence: 99%